Effect of Light Intensity on Growth Rate and Survival of Euphyllia paradivisa Coral Ex-Situ - Luthfy Allyana Damayanti Saqha; I Wayan Arthana; Ni Made Ernawati (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Coral reef ecosystems are vulnerable to damage. The rehabilitation process naturally takes a long time. This study aims to determine the growth rate and survival of Euphyllia paradivisa corals ex-situ at PT Agung Aquatic Marine, Bali. Seawater used in the aquarium has very maintained water quality to keep the corals alive even though they are outside their natural habitat. This research employs an experimental method, with data analysis conducted using the independent sample T-test. We collected data eight times, once every two weeks for four months. Each of the six aquariums, comprising three with sunlight treatment and three with LED light, houses 10 transplanted corals. A caliper is used to measure the width and height of the corals. The growth rate of Euphyllia paradivisa corals under different treatments (sunlight vs. LED light) was determined by analyzing the results. There is a significant difference in the width and height of Euphyllia paradivisa corals. The growth rate of Euphyllia paradivisa corals in ex-situ under the treatment of sunlight is 0.016 mm wide and 0.017 mm high per month, and then in the treatment of LED light, the growth rate of Euphyllia paradivisa corals in ex-situ is 0.009 mm wide and 0.007 mm high per month. The growth rate of Euphyllia paradivisa corals in ex situ with sunlight treatment is better than LED light treatment.